Cross-Architectural Baseline Dataset Generation for SBOM Assessment and Cybersecurity Testing - Kankaansivu, Akseli (2025)
These days, it is common to use ready-made components, libraries, and tools in software development. Using third-party software is a good practice, since it enables the development of large applications, without taking an arduous amount of time. A Software Bill of Materials (SBOM) is a list of all the dependencies used in a software. The point of this study is to investigate cross-compilation for multiple architectures and generate a multi-architectural dataset of binaries from different open-source components for SBOM and security assessments. The dataset includes ELF-executables and object files compiled for x86, ARM, RISC-V, and MIPS architectures using different compiler optimization levels.